Project Benefits of Digital Fabrication in Irregular-Shaped Buildings - Namhyuk Ham; Sanghyo Lee (Advances in Civil Engineering)
The main purpose of this study is to investigate the advantages of digital fabrication pertaining to construction project management, in particular, in terms of different project management factors, using case studies of irregular-shaped buildings in which digital fabrication has versatile applications. This study collected secondary data corresponding to 27 construction projects of irregular-shaped buildings that implemented digital fabrication. Success criteria were developed based on the Project Management Body of Knowledge (PMBOK) to assess the benefits of implementing digital fabrication for management of the considered construction projects of irregular-shaped buildings. Content analysis was performed to investigate the degree of satisfaction for the success criteria of each project. With this approach, it is possible to see which success criterion appears more times as a positive factor and which ones appear as challenges or problems. Among the positive benefits of digital fabrication on construction project management, quality increase and control appeared in the highest number of projects (17 out of 27 projects) at the highest frequency (26 instances). However, among the negative benefits that were mentioned as challenging or causing difficulties of digital fabrication on construction project management, cost reduction and control appeared in the highest number of projects (14 out of 27 projects) at the highest frequency (21 instances). But it does not mean that the use of digital fabrication was overall negative.